Predictors of channel switching during live prime time television advertising - Dix, Stephen Richard (Curtin University, 2006)
The focus of this study is on viewers’ channel switching behaviour during prime-time television advertising breaks. While the extent of channel switching has been studied repeatedly, the factors underlying channelswitching have not been extensively researched within a single study. To date, methodological limitations associated with self-reports, in-home cameras and electronic tracking data have restricted the scope for identifying the predictors of channel switching.The study makes use of a dual observation/survey methodological approach that has been largely overlooked in this area of research. This approach makes it possible to determine the influence of previously untested potential predictors of channel switching. The aim of this study is to determine the influence of six identified predictors on television viewers’ channel switching. The predictor variables tested include Perceived Clutter, Channel Proliferation, Attitude towards Television Advertising, Planned versus Impulse Viewing, Advertising Triggers and Remote Control Device (RCD) Empowerment. The last two predictors (Advertising Triggers and RCD Empowerment) result from factors drawn from a scale (SITUZAP) developed to measure the situational factors associated with channel switching. Moreover, the study determines the impact of these six predictor variables on observed channel switching (observed PROPZAP) across 1,283 observations as well as on reported channel switching (reported PROPZAP) across 848 respondents.The empowerment provided by the RCD emerges as the dominant predictor of channel switching behaviour. Access to the RCD as a means of controlling the viewing environment is the foremost influencer of both observed and reported propensity to switch channels. However, while reported switching propensity is influenced by ‘advertising triggers’ (for example, a repetitive or irritating commercial) and ‘perceived clutter’ (too much advertising on television), observed switching propensity is unaffected by these factors.